PENINGKATAN KESEJAHTERAAN MASYARAKAT MELALUI GERAKAN MANDIRI PANGAN DI RT 5 RW I DESA PRAMBATAN LOR KABUPATEN KUDUS - Aini Indriasih; Yuli Haryati; Dian Ayu Uswatun Hasanah; Einstivina Nuryandani; Edi Prayitno (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2022)
The independent food movement has become a global issue. Fulfillment of food for every household is a goal as well as a target for food security in the region and nationally. This can be done from strengthening food security at the family level by realizing family food independence. Family food independence is carried out by utilizing the yard of the house. The problem occurs when the yard area is decreasing. The narrowness of the land resulted in the interest and attention of residents to continue the culture of utilizing the yard is decreasing and even being forgotten. To overcome this, a systemic and systematic strategy is needed to revive the culture. Re-actualization efforts are needed to revive the culture of planting in the yard. PkM activities aim to improve the socio-economic conditions of the residents by setting aside a little time and energy to cultivate the yard into a source of family food security. The activity was carried out in Prambatan Lor Village, Rt 05 Rw I, Kaliwungu sub-district, Kudus district. Stages of activity: 1) site survey/licensing, 2) theoretical training 3) practical training and 4) monitoring and evaluation. The results of the monitoring carried out showed that the vegetables were starting to grow, while the catfish were in the growth stage. The results of the interview partners felt happy to get new knowledge and were helped in using the yard as a sustainable food house.